ENGAGING VOCATIONAL COLLEGE STUDENTS’ LEARNING THROUGH E- PORTFOLIO BASED DIGITAL MODULE - I Putu Yoga Laksana; I Gusti Ayu Putu Dewi Paramita; Ni Nyoman Yuliantini; Gusti Nyoman Ayu Sukerti; Ni Ketut Suciani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aimed at developing an e-portfolio-based learning module integrated with multi- learning media platforms in engaging students’ learning. Seventy-seven students were involved in this study. They are sophomores at a vocational college in Business Administration Department in the academic year 2021/2022. This study is a research and development typed research by implementing design-based research (DBR) to develop a digital learning module based on e-portfolio principles. Three things were accomplished as a result of this research's implementation. First, the results of the needs analysis of students who are still getting English lectures at this moment (current learners), followed by the findings of observer observations in the classroom learning implementation. Second, the outcomes of designing and creating e- portfolio-based instructional materials in the form of a digital module that is connected to various digital platforms with the aid of QR codes. The analysis findings about the efficiency of using produced electronic modules come in third. The result of the current learners’ perception showed that the implementation of the e-portfolio learning model was able to improve student's learning achievements, however, the urgency in developing a digital module integrated with a multi-learning media platform was necessarily taken into account. Moreover, a digital module was designed based on the students’ needs and digitalization era 4.0. Consequently, the outcome of the digital module's development had a favorable impact on students' engagement to learn in a blended learning environment.